EKSISTENSI PEREMPUAN BATAK TOBA DALAM BUDAYA DAN AGAMA - Grecetinovitria Merliana Butar-butar (JURNAL PIONIR, 2020)
This research entiled The Existence of Batak Toba Women in culture and religion. Purpose of this study was  to determine existence of Batak Toba women in culture and religion . The research method used is qualitative research methods (library research). An understanding of the equal role  of men and womenis not always carried out inlife and civilization in the field of education, customary traditions also in inheritance rights. The church is expected to make the congregation aware of the importance of gender equality and justice without removing the essence of the Batak traditional culture and women should be given space to be decision makers. Keywords : existence, Batak Toba Woman, culture